INTIMACY AND THE THIRST FOR SOFT MASCULINITY: FANFICTION AND K-POP FANS IN INDONESIA - Nurul Laili Nadhifah (Culturalistics: Journal of Cultural, Literary, and Linguistic Studies, 2026)
Fanfiction is a medium for K-Pop fans to portray the idea of their perfect people in the form of their idols. Driven by intimacy formed through parasocial relationship, those fans create stories in an alternative universe, where their idols are not idols anymore but mere humans in certain plots of the story. Since fanfiction about K-Pop idols is common in Indonesia even since the 2nd generation of idols, this study is focused on the characteristics of male characters in Indonesian fanfiction based on Korean Idols. The data, which are fanfictions with the highest ratings, taken from Wattpad as one of the most famous fanfiction sites. Analyzing fanfictions using parasocial relationship and the soft masculinity concept is related to the real condition of society in Indonesia nowadays; this research tries to dig deeper into why soft masculinity is something that those K-Pop fans are longing for. The findings show that indeed, parasocial relationship between idols and fans plays role in pushing K-Pop fans to write fanfinction. Moreover, gender inequality within patriarchal society also triggers female K-Pop fans to write about characters who possess the traits of soft masculinity like tender charisma, purity, and politeness.